Contrasting prevalence of selection and drift in the community structuring of bacteria and microbial eukaryotes. (2nd July 2018) - Logares, Ramiro; Tesson, Sylvie V.M.; Canbäck, Björn; Pontarp, Mikael; Hedlund, Katarina; Rengefors, Karin
Summary: Whether or not communities of microbial eukaryotes are structured in the same way as bacteria is a general and poorly explored question in ecology. Here, we investigated this question in a set of planktonic lake microbiotas in Eastern Antarctica that represent a natural community ecology experiment. Most of the analysed lakes emerged from the sea during the last 6000 years, giving rise to waterbodies that originally contained marine microbiotas and that subsequently evolved into habitats ranging from freshwater to hypersaline. We show that habitat diversification has promoted selection driven by the salinity gradient in bacterial communities (explaining ∼ 72% of taxa turnover), while microeukaryotic counterparts were predominantly structured by ecological drift (∼72% of the turnover). Nevertheless, we also detected a number of microeukaryotes with specific responses to salinity, indicating that albeit minor, selection has had a role in the structuring of specific members of their communities. In sum, we conclude that microeukaryotes and bacteria inhabiting the same communities can be structured predominantly by different processes. This should be considered in future studies aiming to understand the mechanisms that shape microbial assemblages.